Maternal and Foetal Outcomes in Trial of Labour with a Previous Lower Segment Caesarean Section Scar at Sarawak General Hospital, 2010 - Kyaing, Yee Yee; Awi, I.; Mardiana, Binti Kipli; Haris Njoo, Suharjono; Mya, Kyawswa (Malaysian Society of Applied Biology, 2018)
The research aimed to study outcomes of trial of labour in women with a previous LSCS scar in Maternity Unit, Sarawak General Hospital, Malaysia, 2010 and it was designed as retrospective study by reviewing records of pregnant women with a previous caesarean section scar without prior vaginal delivery. Out of 390 women, successful vaginal delivery rate (VBAC) was 53.3%. Blood loss among successful group were significantly less than that of failed group (p=0.018) but blood transfusion was not significantly different between these two groups (p=0.258). Successful VBAC rate was significantly higher in the group of foetal weight between 2.5 to 3.5 Kilogram comparing to the group of more than 3.5 Kilogram (p=0.048). Newborns with Apgar score less than 7 after 1 minute of delivery were more common in failed VBAC than successful VBAC (p=0.026). NICU admission were higher in the group of preterm pregnancy (p <0.001). The study concluded that success rate was about fifty percent. Foetal birth weight was a significant factor for successful VBAC. These results should be considered in trial of labour.